Pengaruh Media Sosial Dan Personal Branding Terhadap Loyalitas Pelanggan Pada Toko Umkm Dessert Fenomenal Tangerang Selatan - Wulandari, Rafika; Maulana Irfanudin, Ahmad (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Abstrak. his study aims to find out the influence between the influence of social media and Personal Branding on customer loyalty both partially and simultaneously. This research was conducted using a quantitative research method involving consumers (100 respondents) as a sample. Also, this researcher used various research tests, namely validity tests, reliability tests, calcium assumption tests, correlation coefficient tests, regression coefficient tests, determination coefficient tests and hypothesis tests. The results of the study obtained the multiple regression equation Y = 1.231 + 0.122 X1 + 0.433 X2 + e. The value of the regression coefficient on the productivity variable of 1.231 concluded that if social media (X1) and Personal Branding (X2) remained (unchanged), then the customer loyalty consistency value (Y) was 1.231. The results of the t-test statistics showed that there was a positive and significant influence of social media on customer loyalty. Based on the calculation of the ttable > (1,984) which is 1.539 and a significant value of 0.127 < 0.05, thus H1 is accepted and Ho is rejected so that there is a partial positive and significant influence of social media on customer loyalty. And, the results of statistical calculations show that the value of F is calculated 550,796 > 3,089. By using a significance limit of 0.05, the significance value is 0.000 < 0.05. This means that the hypothesis that states that the simultaneous variable of social media (X1), Personal Branding (X2), has an influence on customer loyalty (Y) Keywords: Social Media, Personal Branding, Customer Loyalty